BEBAN DAN DISIPLIN KERJA BERPENGARUH TERHADAP KINERJA AWAK KAPAL NEGARA ANDROMEDA - Deni, Muhammad (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2017)
The purpose of this study was to determine the influence of work load and workdiscipline to performance of Crews Ship of the country Andromeda. Population of thisstudy as many as 15 crews. The results of calculations using SPSS, showed that: R2 of0.349 (37.4% ), illustrates that the performance of crews (Y), can be explained by allindependent variables 34.9%, while the remaining 65.1%, can be explained by otherfactors, which are not included in this study. From the result of hypothesis F test ,obtained value of Fcount ( 6.243) > 0.05, means that there is the influence of work loadand work discipline together to crew performance. While the results of the hypothesis ttest, both of two variables there are no influence of them to performance